The Relationship Among Secondary Trauma, Self-Efficacy, and Correctional Nurses. (July 2020) - Wright, Ranee' Maree'
Many of the nurses working in corrections suffer from secondary trauma as a result of taking care of a population that has had a high percentage of traumas in their lives. There is limited research in correctional nursing, and perhaps by identifying the relationship among secondary trauma, self-efficacy, and correctional nursing, there will be growth as a profession. A literature review was completed using PubMed, CIHAHL, and Google Scholar. If nurses apply self-efficacy and secondary traumatic growth into their profession, they will be removing negative emotions from secondary trauma and emergency medical crisis situations. With the correctional populations, it is important for correctional nurses to recognize the barriers in themselves to better take care of their patients. This might then lead to better care and have an impact on the violence in society upon release.